RANPENGARUH ONLINE CONSUMER REVIEW DAN RATING TERHADAP KEPUTUSAN PEMBELIAN GENERASI MILENIAL PADA PENGGUNA MARKETPLACE SHOPEE (STUDI PADA TOKO SHOPEE PROMODAZZLE) - Winoeravisa, Diana (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2020)
The era of globalization has hit all aspects of life, especially technology and communication which continue to experience increasingly sophisticated developments. Technological developments are also accompanied by the rate of population growth in Indonesia which is dominated by the millennial generation, namely residents aged 21 to 41 years. This millennial generation grew up when there were changes in the global economy, which also affected the buying and selling sector which was carried out online using the marketplace. However, the emergence of a marketplace influences the mindset of consumers before purchasing an item or service, one of which is by looking at online reviews and also store ratings given by other consumers. The purpose of this study was to find out and analyze the influence of online consumer reviews and ratings on millennial generation purchasing decisions at the Shopee Promodazzle store. This type of research is quantitative research. The data used in this study is primary data, collected using a questionnaire technique. The sampling technique used in this study was non-probability sampling and the sample used was 100 respondents. The analytical method in this study uses Multiple Linear Regression Analysis The results of the study show that: 1) Online consumer reviews have a positive and significant effect on millennial generation purchasing decisions for marketplace shopee users at the Shopee Promodazzle store. 2) Reviews have a positive and significant effect on millennial generation purchasing decisions for Shopee marketplace users at the Shopee Promodazzle store. 3) Online consumer reviews and ratings together have a positive and significant effect on millennial generation purchasing decisions for Shopee marketplace users at the Shopee Promodazzle store.